"Lift the veil to sell" Concept to Visual Merchandising - Mishra, Aruna kumar; Mishra, Purabee Purnasha (Journal of Entrepreneurship, Business and Economics, 2016)
As the current political scenario is different and new rules are coming for FDI in India, in either case the retailers have to realign their USP and make strategies to meet the current customer require-ments. In the list first comes the store experience now that we are talking of cleaning India as a movement we need to ensure the same in a retail store which will immediately enhance the store ex-perience. As in case here we will see the minimum things we would need to sell better and make the merchandise visible rather than other distractions. This paper is about exploring why and how to design the planogram for visual merchandising of the supermarket for regional indigenous retailers, by taking reference of the other retailers and also common merchandising techniques widely accept-able. The study was done by observation and feed back of the retail professionals. This is case of a retail store found in the main road where small changes can make customer experience better which can be used in other retail outlets also small, big, new, old anyone in such case. Research paper Reference to this paper should be made as follows: Mishra, A.K., Mishra, P. P. (2015). “Lift the veil to sell” Concept to Visual Merchandising: Case of a Supermarket”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 1, pp. 50–80.